Hubungan Penggunaan Kontrasepsi Suntik 3 Bulan dengan Kenaikan Berat Badan pada Wanita Usia Subur di Desa Karangsari Wilayah Kerja Puskesmas Cikelet Kabupaten Garut - Arieb Shintami, Rica; Fitriana, Nana; Rachmawati, Laily; Listyaningsih, Listyaningsih; Rosidah, Rosidah; Nengsih, Nengsih (Jurnal Kesehatan Pertiwi, 2025)
Introduction: Injectable contraceptives are widely used due to their practicality, effectiveness, and affordability. However, their use is frequently associated with side effects, particularly weight gain, which may affect acceptor compliance. Previous studies suggest that long-term exposure to progestin in three-month injectable contraceptives can stimulate appetite through hypothalamic pathways and increase fat storage. Objective: This study aimed to analyze the relationship between the duration of three-month injectable contraceptive use and weight gain among women of reproductive age in Karangsari Village, under the working area of Cikelet Public Health Center, Garut Regency. Methods: A descriptive-analytic study with a cross-sectional design was conducted in September–October 2024. The population consisted of 349 injectable contraceptive acceptors, with 45 respondents selected through purposive sampling based on inclusion criteria. Data collection involved structured questionnaires, contraceptive cards, and standardized weight measurements. Data were analyzed using univariate analysis for frequency distribution and bivariate analysis with Chi-Square tests at a 95% confidence level. Results: Most respondents were aged 20–35 years (68.9%), had secondary education (51.1%), and were unemployed (51.1%). More than half had used injectable contraceptives for over two years (55.6%). Weight gain was observed in 73.3% of respondents. The Chi-Square test revealed a significant association between duration of contraceptive use and weight gain (p = 0.013). Longer use (>2 years) was linked to a higher likelihood of weight gain. Conclusion: The study confirms a significant relationship between prolonged use of three-month injectable contraceptives and weight gain. Health providers are encouraged to deliver adequate counseling, routine monitoring, and lifestyle modification guidance to minimize long-term side effects.